Implementasi Standar Operasional Prosedur Telepon Operator di Sheraton Hotel Bandung - Windy Stevani Siahaan; Dendi Gusnadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the implementation of standard operational procedures and analyze the obstacles or challenges of telephone operators at the Sheraton Bandung Hotel & Towers. This study uses a qualitative method. By collecting data through observation, interviews, document analysis and field notes, with a focus on the interactions and functions of telephone operators in hotels. Data analysis uses narrative analysis to produce in-depth descriptions of telephone operators' experiences and interaction patterns. The data reduction process simplifies and filters information to find the most relevant and significant findings. Interpretation of findings is carried out by connecting them with relevant theory or literature, and the results of the analysis are explained in detail in the research report. The results of this research indicate that the implementation of Standard Operating Procedures (SOP) for telephone operators at the Sheraton Bandung has been carried out successfully, which has had a positive impact on service performance and customer satisfaction. However, despite this, several areas were identified that needed to be improved to achieve a better level of consistency. The challenges and obstacles faced, both technical and non-technical, need to be resolved in order to increase overall service effectiveness.